Exploring the relationship between learning emotion and cognitive behaviors in a digital game - Li Chen; Zehui Zhan; Han Chen; Linlin Zheng (Future in Educational Research)
Abstract Previous studies have primarily explored the learning effects of digital games on students from a macro perspective, mainly ignoring the fine‐grained dimensions of learners' emotions and cognition during gameplay. To enrich the study of learners' emotions and cognitions in the context of digital games, this paper conducts an empirical study using the self‐developed board game “Connect Four Chess” as a research vehicle. We semi‐automatically identify learners' emotional and cognitive behaviors within this game‐based educational context and explore the relationship between the two. The study demonstrates that high‐level learners maintained a high level of insightful emotion throughout the game, excelled at constructing strategic formations to control more significant chessboard areas, and preferred to reserve powerful pieces until the end to secure a winning advantage. Conversely, low‐level learners exhibit a predominant level of neutral emotion, especially during unrelated behaviors, and struggle to maintain a strategic overview, focusing instead on smaller, immediate gains, which hamper the application of deeper strategies.